Factors Affecting Implementation and Compliance with Housing Standards for Sustainable Housing Delivery in Bayelsa State, Nigeria - Eugene Ehimatie Atamewan (European Scientific Journal, ESJ, 2019)
In the quest to find solutions to the ever increasing housing shortages in Nigerian cities, developers, especially the low-income groups, embark on housing construction which in the eye of the government housing agency circumvent compliance to housing standards and are therefore illegal. This research evaluates factors affecting the implementation and compliance with housing standards for sustainable housing delivery in Bayelsa State, Nigeria. The methodology employed was a qualitative research approach involving indepth interviews, physical observations and detailed, systematic and thorough review of literatures on the subject matter from published works of renowned authors. In addition, 20 housing units were selected using purposive sampling technique for detailed study; while respondents of 20 selected housing units used were also interviewed including housing professionals and personnel of housing agencies in the state using both random and expert sampling techniques. From these responses, other factors peculiar to Bayelsa State were outlined. Data collected were analyzed using content analysis. Findings listed factors such as administrative practices, uncertainty of standards, socioeconomic, demographic and socio-cultural factors. Recommendation is that these factors should be considered in developing housing standards for a given area and making the standards flexible in order to make compliance practicable and enforceable.